Influence of Family Dynamics on Stigma Experienced by Patients With Schizophrenia: Mediating Effect of Quality of Life - Wang, Ling; Chen, Yanhua; Hu, Chengping; Qin, Hongyun (Frontiers in Psychiatry, 2021)
Background: Stigma is a barrier to schizophrenia recovery; thus, screening the factors that affect stigma experienced by patients with schizophrenia and exploring the interactions between each factor are critical for improved treatment. The purpose of this study was to demonstrate the relationship between quality of life (QoL), family dynamics, and stigma in patients with schizophrenia. Methods: A total of 447 participants with schizophrenia were recruited in the study, including 281 community patients and 166 inpatients. Three scales, Schizophrenia Quality of Life Scale (SQLS), Self-rating Scale of Systemic Family (SSFD), and Stigma Scale for Mental Illness (SSMI), were respectively used to evaluate three variables: QoL, family dynamics, and stigma. The correlations between each factor in these three scales were evaluated by Spearman’s rank correlation analysis. A mediation model was constructed to investigate whether QoL mediated the relationship between stigma and family dynamics. Results: Correlation analysis revealed that most variables in these three scales correlated significantly with each other. Mediational regression analyses indicated that the degree of stigma was affected by family dynamics, that is, good family dynamics predicted less stigma. Surprisingly, we found that a worse QoL was associated with a less stigma, and this led to good family dynamics being related to a worse QoL. These findings further suggested that QoL had a mediating effect on the relationship between family dynamics and stigma. Conclusions: This study suggested that more attention should be focused on the multifactorial influence of stigma on patients with schizophrenia. Integrated and personalized interventions regarding QoL and family dynamics can be tailored for patients with schizophrenia to reduce self-stigma.